Optical analysis, antioxidant activity and microbiological quality of cold-pressed pumpkin oil - Vesna Đurović; Mirjana Radovanović; Dalibor Tomić; Miloš Marjanović; Leka Mandić (Journal of Central European Agriculture)
Consumer interest in minimally processed food, including cold-pressed oil, is growing year by year, along with evidence of the positive effects of various bioactive ingredients that promote health. This study aimed to characterize the cold-pressed oils obtained from non-intensively grown pumpkins. Some optical characteristics, content of total phenols and antioxidant activity were determined, as well as microbiological analysis of the obtained oils. Cold-pressed pumpkin oils differ in the ranges of specific absorbances: 3.40–7.04 at 232 nm and 1.96–3.33 at 270 nm. The refractive index at 23 °C varies from 1.4700 to 1.4730. The content of total phenols in pumpkin oil ranged from 1.83 to 4.56 mg GAE (gallic acid equivalent)/100 mL. The results of DPPH• (2,2-diphenyl-1-picrylhydrazyl) radical scavenging activities, expressed as % inhibition in the lipophilic fraction from pumpkin oil ranged from 42.48% to 66.91%. The number of bacteria and molds determined was by the Regulations, and sulfite-reducing bacteria were not detected in the oils. Cold-pressed oils are a good source of antioxidants and their use is beneficial for human health.